Manual of recycling. Buildings as sources of materials. - Hillebrandt, Annette; Riegler-Floors, Petra; Rosen, Anja; Seggewies, Johanna (Ed. Detail, 2019)
How is it possible to keep the immense deposits of raw materials in buildings "active" and realise environmentally sustainable buildings in the long term? Besides "sufficiency, consistency and efficiency", this goal implies the intelligent use of resources, the recyclability of structures, circular construction methods that reuse decommissioned materials, in short "urban mining". This requires a rethink in planning and execution, thus posing a great challenge for architects and engineers. The Manual of Recycling provides the necessary expertise for the associated paradigm shift in construction. In addition to successful project examples, this comprehensive and detailed guide provides in-depth explanations on calculation methods and tendering aspects: recyclable construction, urban mining - resource city and buildings, structures that can be dismantled; design and design methodology in the life cycle, detailed guide of relevant construction component connection.
Keywords: Bebauung; Architektur; Gebäude; Baumaterial; Recycling; Kreislaufwirtschaft; Building Information Modeling; Materialeinsatz; Urban Mining; Rohstoff; Ressourcen; Umweltverträglichkeit; Baukonstruktion; Sortenreinheit; Materialverwendung